An implementation framework for vision-based bat-like inverted perching with bi-directionalthrust quadrotor. (January 2022) - Yu, Pengfei; Wong, KC
This paper presents an implementation framework to perform a vision-guided, bat-like inverted perching maneuver with a bi-directional thrust quadrotor platform. The framework consists of several distinct modules (guidance, motion planning, control, state estimation) that can be easily be individually customized in the future to meet specific research requirements. The main contribution of this paper lies in the whole framework pipeline with a modular structure developed for implementing a generalized framework for an agile quadrotor to achieve inverted perching. A computationally-light guidance module has been developed as an example to demonstrate the capability while being independent of accurate pre-known target information, and does not require the state estimation of the quadrotor to be provided by an external motion capture system as in our previous work. A motion planning module based on an optimization method has been introduced to generate a two-stage inverted perching trajectory aiming at minimizing altitude loss during the half-flip maneuver. A control module has been developed to enable a bi-directional quadrotor to fly in both upright and inverted states and closely follow the intended trajectory. The compensation strategy used in the control module is key to minimizing the transition time between the upright and inverted states. Finally, an experimental flight platform has been developed to demonstrate the capabilities of the framework. During testing, the proposed framework has achieved an 80 % success rate. To the best of our knowledge, this paper presents the first time a quadrotor has achieved the inverted perching maneuver using onboard vision guidance.